Manajemen Dalam Peningkatan Mutu Pembelajaran Pendidikan Agama Islam Di Madrasah Aliyah Negeri 2 Surakarta Tahun 2013/2014 - Fajarwanto, Joko; , Dr. Abdullah Aly M.Ag (2016)
ABSTRACTS Management is important rules in teaching learning process because in teaching learning process, management is become tool to help reaching the aim of learning that is infuenced by many factors that have to considered in teaching learning process. In increasing learning process, the rule of headmaster, teacher, students and other element is very important too. Madrasay Aliyah 2 Surakarta is one of school that has islamic basic in teaching learning process. For keeping quality in learning, it is needed sistematic and planned activities in form management. The problem in this research is what the strategies and the model of management in increasing quality of Islamic education in Madrasayh Aliyah Negeri 2 Surakarta. The objectives of this research is to know and to describe the strategies is planning and type of incresing quality of Islamic education in Madrasah Aliyah Negeri 2 Surakarta. The type of this research is field research and research approach in qualitative form. Qualitative reasearch is research that produce data in writing text or verbal from informant. The methode of this research is observation, interview and documentation. The result shows that strategies of plan that is done by Madrasah Aliyah Negeri 2 Surakarta in increasing quality to achieve purpose of Islamic education that can be seen from many aspects such as discusing aspects that relates to islamic education, wether about formal or informal learning and having teamwork with parents. And the type of management is increasing quality of islamic education is organizing in MAN 2 Surakarta is led by head master, comprehending the purpose of Islamic education, identifying activities that are needed, deviding the tasks for teacher, stabilizing the relations between the teachers. Keywords: School Management, Islamic Education, MAN (Islamic Senior High School) 2 of Surakarta